Modelo para prática e avaliação de canteiros de obra sustentáveis – uma visão Lean x Green x Wellbeing - Vasconcelos, Iuri Aragão de (2013)
Among the various philosophies currently widespread, lean construction and green building has gained prominence in the context of technological innovation in construction within the project management. The concept of social responsibility has also gained importance in the strategy of companies in this sector towards the satisfaction of its employees, that in this work is treated as quality of life and welfare in construction (wellbeing). It is possible to identify a potential simultaneous interaction between these components (lean, green and wellbeing) with the philosophy of sustainability, which employs three main pillars (economic, social and environmental). There are models that attest to maturity of green, social responsibility and involvement with lean construction by firms. However, the simultaneous interaction between these philosophies in favor of sustainable development, has been little explored. Moreover, the building process, which is considered one of the stages of generating greater ecological damage is directly related to the management of the construction site, and even then, these assessment methodologies seek to analyze the company holistically or even giving emphasis on the development of the projects, indicating the need to seek studies specifically focused on sustainable construction sites. Therefore, the objective of this research is to propose a model of guidelines for practice and evaluation of sustainable construction sites, aiming the interaction between lean, green and wellbeing. The methodology used in the research was: a literature review, for information and data on the topic of best practices and performance indicators for sustainable construction sites, followed by developing the model and, finally, the realization of a field study within 3 construction works in Fortaleza / CE to test the use of the model. The result of this research is the achievement of sustainability degrees of construction sites and the behavior of firms in this context, through a better understanding of the principles advocated by lean, green and wellbeing and its relation to the philosophy of sustainability, focusing on the application of these concepts on construction sites through the proposed model